The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Arboricultural cut type and pruning severity can alter the arboreal invertebrate community for at least two years - Stella R. Dee; Michael J. Cunningham-Minnick; Athena P. Vasilopoulos; Brian Kane (Urban Forestry & Urban Greening, 2026)

Forward osmosis followed by reverse osmosis for the removal of contaminants of emerging concern using a CO2-responsive draw agent - Rachel S. Korchinsky; José Giovanni L. Brito; Louis Fieldhouse; Pascale Champagne; Michael F. Cunningham; Philip G. Jessop (Journal of Hazardous Materials, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Apex Scavenger Declines Have Cascading Effects on Soil Biogeochemistry and Ecosystem Processes - Torrey Stephenson; David W. Crowder; Ernest Osburn; Michael Strickland; Menna Jones; Savannah Bartel; Kawinwit Kittipalawattanapol; Calum X. Cunningham; Tara Hudiburg; Andrew Storfer; Julia Piaskowski; Laurel Lynch (Global Change Biology, 2025)
Global apex scavenger declines strongly alter food web dynamics, but studies rarely test whether trophic downgrading impacts ecosystem functions. Here, we leverage a unique, disease‐induced gradient in Tasmanian devil ( Sarcophilus harrisii ) population densities to assess feedbacks between carcass persistence, subordinate scavenger guilds, and biogeochemical cycling. We further explored interkingdom and seasonal interactions by manipulating carcass access and replicating experiments in warmer, drier summer versus cooler, wetter winter periods. We show Tasmanian devil declines significantly extend carcass persistence and increase the flux of carcass‐derived nutrients belowground (e.g., by 18–134‐fold for ammonium). Greater nutrient availability reduces soil microbiome diversity by up to 26%, increasing the relative abundance of putative zoonotic pathogens. Nutrient subsidies also shift microbial communities toward faster‐growing taxa that invest less energy in resource acquisition, with implications for soil carbon sequestration. Rates of carcass decomposition were reduced in the winter, dampening soil biogeochemical responses and interkingdom competition. Notably, while less efficient scavenger guilds clearly facilitate carcass consumption, they were not able to fill the functional role of apex scavengers. Our study illustrates how trophic downgrading effects can ripple across all levels of ecological organization.

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Misspecifying Sex‐Structured Dynamics in Stock Assessment Models - Matthew L. H. Cheng; Daniel R. Goethel; Peter‐John F. Hulson; Michael J. Wilberg; Craig Marsh; Curry J. Cunningham (Fish and Fisheries, 2025)
Sex‐specific variation in population demography and life‐history traits (e.g., growth, natural mortality) is common in many fish populations. Differences in these processes by sex can dictate population dynamics and influence how harvesters interact with the resource. Across various fisheries management systems, stock assessment models (SAMs), which mathematically represent population age and/or size structure, are widely utilised to estimate fish population status and provide sustainable harvest recommendations. However, few studies have examined the implications of alternative modelling assumptions when incorporating sex‐specific dynamics in SAMs. For instance, the impacts of simultaneously ignoring sex‐specific variations in growth, selectivity, and natural mortality on SAM performance have not been explored. In this study, a simulation‐estimation framework was developed for a sexually dimorphic fish population to: (1) assess the consequences of ignoring sexual dimorphism (i.e., growth, natural mortality, and selectivity) and the benefits of using sex‐specific catch data to inform the estimation of these processes, (2) evaluate the implications of incorrect modelling assumptions regarding sex ratio at birth, and (3) develop advice for parameterising observation likelihoods to describe sex‐specific composition data. Correctly parameterising sex‐specific variation in life‐history traits led to more robust population estimates and catch advice. Conversely, SAMs ignoring these variations yielded biased estimates of biomass and harvest recommendations. Collectively, our results underscore that oversimplified assumptions about sex‐specific variations in SAMs can lead to poor management advice. Moreover, results emphasise the need for routine collection of sex‐specific data to support the development of biologically realistic models.

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Free radical copolymerization kinetics of bio-based dibutyl itaconate and n-butyl acrylate - Tomaž Pirman; Connor A. Sanders; Martin Ocepek; Michael F. Cunningham; Blaž Likozar; Robin A. Hutchinson (Chemical Engineering Journal, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

BASIS: BioAnalysis SEDFIT integrated software for cGMP analysis of SV-AUC data - Alexander E. Yarawsky; Erik S. Gough; Valeria Zai-Rose; Natalya I. Figueroa; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2024)

How phase transfer increases the number of kinetic regimes from three to seven in nitroxide mediated polymerization of n-butyl acrylate in aqueous miniemulsion - Elnaz Zeinali; Yoshi W. Marien; Sean R. George; Michael F. Cunningham; Dagmar R. D'hooge; Paul H.M. Van Steenberge (Chemical Engineering Journal, 2023)

AAV analysis by sedimentation velocity analytical ultracentrifugation: beyond empty and full capsids - Alexander E. Yarawsky; Valeria Zai-Rose; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison Between Ground, Helicopter, and Unmanned Aircraft System Magnetic Datasets: A Case Study from the Abitibi Greenstone Belt, Canada - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2022)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Inversion of Magnetic Data Acquired with a Rotary-Wing Unmanned Aircraft System for Gold Exploration - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2021)

Utility of DNA barcoding in native Oreochromis species - Tonna O. Mojekwu; Michael J. Cunningham; Roger I. Bills; Petrus C. Pretorius; Thierry B. Hoareau (Journal of Fish Biology, 2021)
The importance of Oreochromis in worldwide aquaculture and regional fisheries motivates the study of their genetic diversity in their native range. In this article, all mitochondrial cytochrome c oxidase subunit I gene (COI) sequences of Oreochromis species are retrieved from Barcode of Life Data system to quantify the available DNA barcoding information from wild individuals collected within the native ranges of the respective species. It is found that 70% of the known species in the genus still lack a COI barcode, and only 15% of the available sequences are from within the respective native ranges. Many of the available sequences have been produced from specimens acquired from aquaculture and introduced, naturalized populations, making the assessment of variation within the original native range challenging. Analyses of the wild‐collected fraction of available sequences indicated the presence of cryptic lineages within Nile tilapia Oreochromis niloticus and O. schwebischi , the occurrence of potential introgressive hybridization between O. niloticus and blue tilapia O. aureus , and potential ancestral polymorphism between Karonga tilapia O. karongae and black tilapia O. placidus . This article also reports a case of misidentification of O. mweruensis as longfin tilapia O. macrochir . These results stress the importance of improving the knowledge of genetic variation within the native ranges of Oreochromis species for better‐informed conservation of these natural resources.

Marker associations for fusiform rust resistance in a clonal population of loblolly pine (Pinus taeda, L.) - W. Patrick Cumbie; Dudley A. Huber; Victor C. Steel; William Rottmann; Christina Cannistra; Les Pearson; Michael Cunningham (Tree Genetics & Genomes, 2020)

Estimates of Blood Lead Levels (BLLs) for Children in Coastal Madagascar: Accounting for Dietary Uptake of Lead (Pb) - D. Brad Akers; Adaline Buerck; Michael F. MacCarthy; Jeffrey A. Cunningham; James R. Mihelcic (Exposure and Health, 2020)

Stroke Induces Prolonged Changes in Lipid Metabolism, the Liver and Body Composition in Mice - Michael J. Haley; Claire S. White; Daisy Roberts; Kelly O’Toole; Catriona J. Cunningham; Jack Rivers-Auty; Conor O’Boyle; Conor Lane; Oliver Heaney; Stuart M. Allan; Catherine B. Lawrence (Translational Stroke Research, 2020)
During recovery, stroke patients are at risk of developing long-term complications that impact quality of life, including changes in body weight and composition, depression and anxiety, as well as an increased risk of subsequent vascular events. The aetiologies and time-course of these post-stroke complications have not been extensively studied and are poorly understood. Therefore, we assessed long-term changes in body composition, metabolic markers and behaviour after middle cerebral artery occlusion in mice. These outcomes were also studied in the context of obesity, a common stroke co-morbidity proposed to protect against post-stroke weight loss in patients. We found that stroke induced long-term changes in body composition, characterised by a sustained loss of fat mass with a recovery of lean weight loss. These global changes in response to stroke were accompanied by an altered lipid profile (increased plasma free fatty acids and triglycerides) and increased adipokine release at 60 days. After stroke, the liver also showed histological changes indicative of liver damage and a decrease in plasma alanine aminotransferase (ALT) was observed. Stroke induced depression and anxiety-like behaviours in mice, illustrated by deficits in exploration, nest building and burrowing behaviours. When initial infarct volumes were matched between mice with and without comorbid obesity, these outcomes were not drastically altered. Overall, we found that stroke induced long-term changes in depressive/anxiety-like behaviours, and changes in plasma lipids, adipokines and the liver that may impact negatively on future vascular health.

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles - Brittany N. J. Davis; Jeffrey W. Santoso; Michaela J. Walker; Catherine E. Oliver; Michael M. Cunningham; Christian A. Boehm; Danielle Dawes; Samantha L. Lasater; Kim Huffman; William E. Kraus; George A. Truskey (Annals of Biomedical Engineering, 2019)

Separation, banking, and quality control of peripheral blood mononuclear cells from whole blood of melanoma patients - Martha Holland; Rachel Cunningham; Lake Seymour; Katja Kleinsteuber; Amy Cunningham; Tara Patel; Michael Manos; Ryan Brennick; Jun Zhou; F. Stephen Hodi; Mariano Severgnini (Cell and Tissue Banking, 2018)

Aeromagnetic Surveying with a Rotary-Wing Unmanned Aircraft System: A Case Study from a Zinc Deposit in Nash Creek, New Brunswick, Canada - Michael Cunningham; Claire Samson; Alan Wood; Ian Cook (Pure and Applied Geophysics, 2018)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Population biology and epidemiology of plant virus epidemics: from tripartite to tritrophic interactions - Michael Jeger; Ziyang Chen; Eleanor Cunningham; George Martin; Glen Powell (European Journal of Plant Pathology, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Southern Hardwood Varietal Forestry: A New Approach to Short-Rotation Woody Crops for Biomass Energy - Scott Merkle; Michael Cunningham (Journal of Forestry, 2011)
Varietal forestry appears poised to make significant contributions to the production of woody crops for timber, pulp and paper, and biomass energy in the southeastern United States. The projected productivity gains with southern pine somatic seedling technology make a strong case for adopting parallel technologies with southern hardwoods. Systems for producing somatic seedlings of multiple southern hardwoods have been developed and in some aspects are already more amenable to scale-up and manipulation than conifer systems. The feasibility of scaling up production of elite, varietal hardwoods using somatic embryogenesis has already been established. By combining this propagation system with hybrid breeding, thousands of somatic seedlings of elite hybrid sweetgum and hybrid yellow-poplar have been generated, some of which have shown impressive biomass productivity in field tests. Varietal, blight-resistant chestnuts now being developed may have even greater potential to be deployed for biomass plantations and other applications in the southern Appalachians.

Short-rotation woody crops for bioenergy and biofuels applications - Maud Hinchee; William Rottmann; Lauren Mullinax; Chunsheng Zhang; Shujun Chang; Michael Cunningham; Leslie Pearson; Narender Nehra (In Vitro Cellular & Developmental Biology - Plant, 2009)

Resource allocation in a social wasp: effects of breeding system and life cycle on reproductive decisions - ELIZABETH L. JOHNSON; TYLER W. CUNNINGHAM; SARAH M. MARRINER; JENNIFER L. KOVACS; BRENDAN G. HUNT; DIMPAL B. BHAKTA; MICHAEL A. D. GOODISMAN (Molecular Ecology, 2009)
Organisms must make important decisions on how to allocate resources to reproduction. We investigated allocation decisions in the social wasp Vespula maculifrons to understand how social insects make reproductive choices. We first determined how annual colonies apportioned resources to growth and reproduction by analysing developing brood. In contrast to expectations, colonies invested in both growth (workers) and reproduction (males) simultaneously. In addition, colonies showed evidence of producing males in pulses and reversing their reproductive choices by decreasing investment in males late in the season. This reversal is consistent with theory suggesting that colonies decrease production in males if fitness of late emerging males is low. To further investigate reproductive decisions within colonies, we determined if the male mates of multiply‐mated queens varied in their reproductive success over time. Sperm use by queens did vary over time suggesting that male success may depend on sperm clumping within the female reproductive tract. Finally, we tested if colony sex ratio conformed to expectations under kin selection theory that nestmate relatedness would positively correlate with investment in new queens if workers controlled sex allocation. Surprisingly, the proportion of queens produced by colonies was negatively correlated with nestmate relatedness, suggesting that allocation may be shaped by advantages arising from increased genetic diversity resulting from multiple mating by queens. Overall, our study suggests that the reproductive decisions of colonies are flexible and may depend both on environmental cues arising from energetic needs of the colony and genetic cues arising from mating behaviours of queens.

The Combined Effects of Remnant Vegetation and Tree Planting on Farmland Birds - ROSS B. CUNNINGHAM; DAVID B. LINDENMAYER; MASON CRANE; DAMIAN MICHAEL; CHRISTOPHER MacGREGOR; REBECCA MONTAGUE‐DRAKE; JOERN FISCHER (Conservation Biology, 2008)
Biodiversity conservation on agricultural land is a major issue worldwide. We estimated separate and joint effects of remnant native woodland vegetation and recent tree plantings on birds on farms (approximately 500–1000 ha) in the heavily cleared wheat and sheep belt of southern Australia. Much of the variation (>70%) in bird responses was explained by 3 factors: remnant native‐vegetation attributes (native grassland, scattered paddock trees, patches of remnant native woodland); presence or absence of planted native trees; and the size and shape of tree plantings. In terms of the number of species, remnant native vegetation was more important than tree planting, in a 3:1 ratio, approximately. Farms with high values for remnant native vegetation were those most likely to support declining or vulnerable species, although some individual species of conservation concern occurred on farms with large plantings. Farm management for improved bird conservation should account for the cumulative and complementary contributions of many components of remnant native‐vegetation cover (e.g., scattered paddock trees and fallen timber) as well as areas of restored native vegetation.

Genetic consequences of habitat fragmentation and loss: the case of the Florida black bear (Ursus americanus floridanus) - Jeremy D. Dixon; Madan K. Oli; Michael C. Wooten; Thomas H. Eason; J. Walter McCown; Mark W. Cunningham (Conservation Genetics, 2007)

Patterns of fish deformities and their association with trematode cysts in the Willamette River, Oregon - Michael E. Cunningham; Douglas F. Markle; Virginia G. Watral; Michael L. Kent; Larry R. Curtis (Environmental Biology of Fishes, 2005)

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening - Juanliang Cai; Barbara K. Goodman; Ankita S. Patel; John B. Mulliken; Lionel Van Maldergem; George E. Hoganson; William A. Paznekas; Ziva Ben-Neriah; Ruth Sheffer; Michael L. Cunningham; Donna L. Daentl; Ethylin Wang Jabs (Human Genetics, 2003)

Influence of nitrogen, photoperiod, cutting type, and clone on root and shoot development of rooted stem cuttings of sweetgum - Heidi Rieckermann; Barry Goldfarb; Michael W. Cunningham; Robert C. Kellison (New Forests, 1999)

Analysis of the human Sonic Hedgehog coding and promoter regions in sacral agenesis, triphalangeal thumb, and mirror polydactyly - F. R. Vargas; E. Roessler; Karin Gaudenz; E. Belloni; Alexander S. Whitehead; Peader N. Kirke; James L. Mills; George Hooper; Roger E. Stevenson; Isabel Cordeiro; Patricia Correia; Temis Felix; et al. (Human Genetics, 1998)

Vocal learning in White-crowned Sparrows: sensitive phase and song dialects - Michael A. Cunningham; Myron Charles Baker (Behavioral Ecology and Sociobiology, 1983)

The role of male vs male interactions in maintaining population dialect structure - Myron Charles Baker; Daniel B. Thompson; Gregory L. Sherman; Michael A. Cunningham (Behavioral Ecology and Sociobiology, 1981)

Effect of date and method of kill on yield, specific gravity and other quality factors of maine potatoes - G. L. Terman; C. E. Cunningham; Michael Goven (American Journal of Potato Research, 1952)

Potato vine killing methods as related to rate of kill, vascular discoloration, and virus disease spread - C. E. Cunningham; P. J. Eastman; Michael Goven (American Journal of Potato Research, 1952)

Effect of storage temperature and size on French fry quality, shrinkage and specific gravity of Maine potatoes - G. L. Terman; Michael Goven; C. E. Cunningham (American Journal of Potato Research, 1950)